Dual‐Function, Tunable, Nitrogen‐Doped Carbon for High‐Performance Li Metal–Sulfur Full Cell. Issue 5 (11th January 2019) - Li, Hongyan; Cheng, Zheng; Natan, Avi; Hafez, Ahmed M.; Cao, Daxian; Yang, Yang; Zhu, Hongli
Abstract: Lithium metal–sulfur (Li–S) batteries are attracting broad interest because of their high capacity. However, the batteries experience the polysulfide shuttle effect in cathode and dendrite growth in the Li metal anode. Herein, a bifunctional and tunable mesoporous carbon sphere (MCS) that simultaneously boosts the performance of the sulfur cathode and the Li anode is designed. The MCS homogenizes the flux of Li ions and inhibits the growth of Li dendrites due to its honeycomb structure with high surface area and abundance of nitrogen sites. The Li@MCS cell exhibits a small overpotential of 29 mV and long cycling performance of 350 h under the current density of 1 mA cm ‐2 . Upon covering one layer of amorphous carbon on the MCS (CMCS), an individual carbon cage is able to encapsulate sulfur inside and reduce the polysulfide shuttle, which improves the cycling stability of the Li–S battery. As a result, the S@CMCS has a maximum capacity of 411 mAh g ‐1 for 200 cycles at a current density of 3350 mA g ‐1 . Based on the excellent performance, the full Li–S cell assembled with Li@MCS anode and S@CMCS cathode shows much higher capacity than a cell assembled with Li@Cu anode and S@CMCS cathode. Abstract : This work realizes the concept of "two in one" for full lithium metal–sulfur (Li–S) batteries . A mesoporous carbon sphere (MCS) is developed for boosting the electrochemical performance of Li–S batteries. 1) the MCS with closed mesoporous structure effectively tackles the shuttle effect in sulfur cathode; 2) the nitrogen‐doped MCS efficiently suppresses dendrite formation in Li metal anode.